Orientalism and Ottoman Modernisation in the Discourse of Postmodernism - Rzayeva, Prof. Roida (European Journal of Multidisciplinary Studies, 2019)
If Orientalism is the critique of modernity, it can be rather considered in a postmodern discourse. New phenomena of global politics, changing moods of mind and cultural discourses again make Orientalism a topical subject. The East has always meant contrast for the West. Yet has it always meant the same? One should particularly note herein a philosophic approach to the problem is necessary instead of the usual and conventional political one, which mostly expresses a unilateral traditional characteristic of Orientalism and interprets it accordingly. There is an opinion Orientalism makes up a paradigm to study non-European histories and cultures using approaches coming after structuralism and postmodernism. As modernized, the East meets/clashes the West while there is no such an opposition in postmodernism, but is co-existence, which echoes the opposition characteristics of Orientalism, unlike the traditional one. At the same time, when analyzing orientalists’ works, we often see not a unilateral, but a synthesized approach e.g in those by Turkish one, Hamdi. In any case, many panels by orientalist artists represent combinations which follow a well-known postmodernist motto, both that and the other, unlike the modern world’s modernist logic, either that or this.